Assessing Acceptability of a Diagnostic and Malaria Treatment Package Delivered by Community Health Workers in Malaria-Endemic Settings of Burkina Faso, Nigeria, and Uganda - Jegede, Ayodele S. (Clin Infect Dis, 2016)
Background. The efficacy of artemisinin-based combination therapy (ACT) and rectal artesunate for severe malaria in children is proven. However, acceptability of a package of interventions that included use of malaria rapid diagnostic tests (RDTs), ACTs, and rectal artesunate when provided by community health workers (CHWs) is uncertain. This study assessed acceptability of use of CHWs for case management of malaria using RDTs, ACTs, and rectal artesunate. Methods. The study was carried out in Burkina Faso, Nigeria, and Uganda in 2015 toward the end of an intervention using CHWs to provide diagnosis and treatment. Focus group discussions (FGDs) and key informant interviews (KIIs) were conducted with parents of sick children, community leaders, and health workers to understand whether they accepted the package for case management of malaria using CHWs. Transcripts from FGDs and KII recordings were analyzed using content analysis. The findings were described, interpreted, and reported in the form of narratives. Results. Treatment of malaria using the CHWs was acceptable to caregivers and communities. The CHWs were perceived to be accessible, diligent, and effective. There were no physical, social, or cultural barriers to accessing the CHWs’ services. Respondents were extremely positive about the intervention and were concerned that CHWs had limited financial and nonfinancial incentives that would reduce their motivation and willingness to continue. Conclusions. Treatment of malaria using CHWs was fully accepted. CHWs should be compensated, trained, and well supervised. Clinical Trials Registration. ISRCTN13858170.